Professional choice and adolescence: old issues, new reflections (Research, Society and Development, 2022)
The decision regarding the professional choice occurs concomitantly with the uncertainties arising from adolescence, in view of the prematurity of this choice, it is clear that adolescents may not be mature for such a decision, risking being influenced by many aspects, especially their family members, peers and the maturity of the subject. Thus, this article aims to understand the main factors that interfere in the adolescent's professional choice. The method used was the integrative literature review, based on scientific articles displayed on LILACS and SCIELO platforms published between 2010 and 2020 in Portuguese and Spanish. Considering this scenario, it is noteworthy that it was possible through this work to determine the main factors that interfere in the adolescent's professional choice, such as family relationships, maturity, self-knowledge and socioeconomic aspects. In this way, the importance of professional guidance for an assertive and satisfactory choice is highlighted, since it can enable young people to self-knowledge, helping them to face this decision and facilitating their insertion in the job market, promoting autonomy and well-being.